Effectiveness of Spinal Stabilization Exercises on Dynamic Balance in Adults with Chronic Low Back Pain - Yousef M. Alshehre; Khalid Alkhathami; Kelli Brizzolara; Mark Weber; Sharon Wang-Price (North American Sports Medicine Institute, 2023)
# Background Dynamic balance is a vital aspect of everyday life. It is important to incorporate an exercise program that is useful for maintaining and improving balance in patients with chronic low back pain (CLBP). However, there is a lack of evidence supporting the effectiveness of spinal stabilization exercises (SSEs) on improving dynamic balance. # Purpose To determine the effectiveness of SSEs on dynamic balance in adults with CLBP. # Study Design A double-blind randomized clinical trial. # Methods Forty participants with CLBP were assigned randomly into either an SSE group or a general exercise (GE) group, which consisted of flexibility and range-of-motion exercises. Participants attended a total of four to eight supervised physical therapy (PT) sessions and performed their assigned exercises at home in the first four weeks of the eight-week intervention. In the last four weeks, the participants performed their exercises at home with no supervised PT sessions. Participants' dynamic balance was measured using the Y-Balance Test (YBT) and the normalized composite scores, Numeric Pain Rating Scale and Modified Oswestry Low Back Pain Disability Questionnaire scores were collected at baseline, two weeks, four weeks, and eight weeks. # Results A significant difference between groups from two weeks to four weeks (*p* = 0.002) was found, with the SSE group demonstrating higher YBT composite scores than the GE group. However, there were no significant between-group differences from baseline to two weeks (*p* =0.098), and from four weeks to eight weeks (*p* = 0.413). # Conclusions Supervised SSEs were superior to GEs in improving dynamic balance for the first four weeks after initiating intervention in adults with CLBP. However, GEs appeared to have an effect equivalent to that of SSEs after 8-week intervention. # Levels of Evidence 1b.